Origin Pattern Care of Orphanage in Developing Children`s Social Skills - Rohmatin, Syifa (International Journal Pedagogy of Social Studies, 2020)
This research is motivated by phenomena that occur and are faced by children in orphanages, which is related to the problem of transition of residence, different characteristics and backgrounds of children, but requires them to be able to adapt themselves to the orphanage environment. Therefore social skills become a capital that must be possessed by children. The purpose of this study is to describe the parenting practices adopted by the orphanage caretaker in developing children's social skills, know how the implementation of parenting is applied, inhibiting factors, and the efforts made by the orphanage caretaker in developing children's social skills. This study used a qualitative approach with descriptive methods. Data collection techniques are done by observation, deep interview, and documentation. The findings of the research revealed that: (1) The pattern of adoption is democratic parenting which is illustrated through the form of care provided. (2) Implementation of parenting that is applied is through several processes, namely adaptation carried out through an interpersonal approach, Goal attainment is done through the inculcation of social values, Integration is carried out through communication and coordination between parties, and Latency which is carried out through routine evaluation. (3) The inhibiting factors experienced are the limitations of caregivers, different backgrounds and characteristics of children, and environmental factors. (4) Efforts which made are the caretaker and caregivers to establish good coordination and communication, take a personal approach to each child, give advice, reprimand, punishment and motivation, establish coordination with the school, and conduct regular evaluations.